Multiplicative Triple Fibonacci Sequence of Third Order (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Coupled Fibonacci Sequence are Firstly established by K.T. Atanassov in 1985. The abstractions of Fibonacci Triple Sequence are considered in 1987. Fibonacci Sequence stands as a kind of super sequence with Fabulous properties. This is the explosive development in the region of Fibonacci Sequence. Fibonacci was advanced by Leonardo de Pisa (whose nickname was Fibonacci, which means son of Bonacci) in 1202 as a result of his inspection on the growth of a population of rabbits. The consecutive Fibonacci numbers are produced by adding together the two previous numbers in the sequence, after specifying suitable initial conditions. In the last years Triple Fibonacci Sequence are hype, but Multiplicative Triple Sequence of Recurrence Relations are less known. Much work has been done to study on Fibonacci Triple Sequence in Additive form. In 1995, Multiplicative Coupled Fibonacci Sequence are contemplated. Our purpose of this paper to present some results of Multiplicative Triple Fibonacci Sequence of third order under one specific scheme.This paper expanded out of a curiosity in the Fibonacci sequence and a craving to spread the results of Multiplicative Coupled Fibonacci sequence. Ever since Fibonacci (Leonardo of Pisa) wrote his Liber Abbaci in 1202, his fascinating sequence has transfixed men through the centuries, not only for its inborn mathematical riches, but also for its applications in art and nature. Indeed, it is almost true to say that the research produced by its nearly amounts to the quantity of off- spring generated by the mythical pair of rabbits who started Fibonacci off on the problem.